Antihypertensive drug utilization pattern and awareness in diabetic hypertensive patients at tertiary care centre - Khrime, Dorchhom; Kumar, Alok; Pandey, Amar Nath; Bansal, Nitin; Sharma, Utkarsh; Varma, Amit (International Journal of Research in Medical Sciences, 2017)
Background: Patients with diabetes has 2 fold higher chances of suffering from hypertension. Hypertension is risk factor for development of diabetes as well for complications like nephropathy, CAD and neuropathy etc. Hypertension control is vital to prevent and retard progression of microvascular and macrovascular complications. Therefore, we undertook this study to evaluate treatment patterns in diabetic patients with hypertension, those are being followed at our institute. Methods: Study group comprised of diabetic patients who had hypertension as well. All patients with diabetes reporting to medicine OPD from March 2014 to September 2014 at our institute were screened. Patients with follow up of at least 3 months and age more than 18 years of either sex were included. Results: There were 223 patients. Study group comprised of 121 males and 102 females. Mean age of group was 48.6 years. One hundred three patients (46.18%) were on monotherapy and remaining 120 patients were on combination antihypertensive drugs. There were total 398 antihypertensive drug exposures. Patient needed mean antihypertensive drug of 1.78. Angiotensin receptor blockers were the most commonly prescribed drugs. Angiotensin inhibitors (angiotensin receptor blockers and ACE inhibitors) were utilized in 158 (71%) patients. Hypertension control was achieved in 84 (37.66%) patients. One hundred eighty one patients (81.2%) knew about disease. Conclusion: Our study showed that majority of diabetic hypertensive patients needed multiple drug therapy to control hypertension. Most of the patients were on ARBs/ACE inhibitors. This was according to recommendation by ADA or JNC8.